Intraoperative management of a hybrid extracorporeal membrane oxygenation circuit for lung transplantation. Issue 12 (16th September 2020) - Martin, Archer Kilbourne; Harrison, Barry A.; Fritz, Ashley Virginia; Landolfo, Kevin P.; Makey, Ian A.; Sareyyupoglu, Basar; Brown, Thomas E.; Johnson, James L.; Pham, Si M.; Thomas, Mathew
Abstract: Background: The use of extracorporeal circulation (ECC) for intraoperative cardiopulmonary support during lung transplantation has been increasing in the recent years. Our group previously described a novel hybrid extracorporeal membrane oxygenation (ECMO) circuit for use in lung transplantation. Technique: Our approach for intraoperative management of our novel hybrid ECMO circuit for lung transplantation is driven by two main goals: The first is to deliver management that ensures an appropriate balance between the native and ECMO cardiac outputs in order to provide a stable environment that promotes attenuation of ischemic‐reperfusion injury during implantation. The second is to provide a stable hemodynamic environment that results in an appropriate global perfusion guided by multiple monitors and an organ systems‐based approach during implantation. Comments: Our novel technique for intraoperative management of this circuit during lung transplantation is described.